How Does Landscape Modification Induce Biological Homogenization in Tropical Stream Metacommunities? - Siqueira, Tadeu [UNESP]; Lacerda, Camila Giaj-Levra Teixeira [UNESP]; Saito, Victor S. (Wiley, 2015)
Habitat modification can homogenize biological communities. Beta diversity analyses provide key information for understanding biotic homogenization, especially given recent conceptual and methodological advances. Here, we investigated if landscape modification was associated with taxonomic homogenization in 32 stream insect communities from the Brazilian Atlantic Forest. We investigated: (1) if the way we defined landscape affected our estimates of beta diversity; (2) to what extent changes in species composition versus relative abundance caused the observed homogenization; and (3) if environmental heterogeneity among modified habitats influenced homogenization. We detected taxonomic homogenization caused by landscape modification only when we used refined landscape categorizations and abundance-based diversity measures. For forested streams, changes in relative abundance rather than absolute taxonomic composition increased the biological variation. Forested streams were generally more heterogeneous, with a variable set of abundant genera; by contrast, non-forested streams were more homogeneous, with the same set of genera being more or less abundant. We suggest that landscape modification by agriculture, pasture, and silviculture reduces beta diversity by limiting the colonization of potential species, and, ultimately, causing taxonomic homogenization. Studies investigating biotic homogenization should include multiple dissimilarity measures representing changes in relative species abundance and community composition.
Keywords: Atlantic forest; Beta diversity; Brazil; Dissimilarity coefficients; Environmental harshness; Stream macroinvertebrates